Ablation of soft tissue tumours by long needle variable electrode-geometry electrochemotherapy: final report from a single-arm, single-centre phase-2 study - Simioni, Andrea (Sci Rep, 2020)
Standard electrochemotherapy (ECT) is effective in many tumour types but is confined to the treatment of small superficial lesions. Variable electrode-geometry ECT (VEG-ECT) may overcome these limitations by using long freely-placeable electrodes. Patients with bulky or deep-seated soft-tissue malignancies not amenable to resection participated in a single-arm phase-2 study (ISRCTN.11667954) and received a single course of VEG-ECT with intravenous bleomycin (15,000 IU/m(2)) and concomitant electric pulses applied through an adjustable electrode array. The primary outcome was radiologic complete response rate (CRR) per RECIST; secondary endpoints included feasibility, metabolic response, toxicity (CTCAE), local progression-free survival (LPFS) and patient perception (EQ-5D). During 2009–2014, we enrolled 30 patients with trunk/limb sarcomas, melanoma, Merkel-cell carcinoma, and colorectal/lung cancer. Median tumour size was 4.7 cm. Electrode probes were placed under US/TC guidance (28 and 2 patients, respectively). Median procedure duration was 80 minutes. Tumour coverage rate was 97% (29 of 30 patients). Perioperative side-effects were negligible; one patient experienced grade-3 ulceration and infection. One-month (18)F-FDG-SUV decreased by 86%; CRR was 63% (95% CI 44–79%). Local control was durable in 24 of 30 patients (two-year LPFS, 62%). Patients reported an improvement in “usual activities”, “anxiety/depression”, and “overall health” scores. VEG-ECT demonstrated encouraging antitumour activity in soft-tissue malignancies; a single course of treatment produced high and durable responses, with low complications.